Parental Involvement in Education and Academic Achievement in Adolescents With Attention Deficit Hyperactivity Disorder. (September 2022) - Musabelliu, Gladiola; Wiener, Judith; Rogers, Maria
This study examined the relationship between parental involvement in education (PIE) and adolescent academic achievement in 99 adolescents with and without ADHD. PIE was measured by two parent-report questionnaires. A standardized test was used to measure academic achievement. Adolescent ADHD status predicted academic achievement. Maternal PIE did not predict adolescent achievement over and above adolescent ADHD status. Fathers' self-efficacy, supportive involvement, and aspirations moderated the association between adolescent ADHD status and adolescent achievement. These PIE variables were positively associated with achievement in adolescents with ADHD. Paternal self-efficacy was not associated with achievement in adolescents without ADHD, and paternal supportive involvement and paternal aspirations predicted lower achievement in these adolescents. These results suggest the importance of paternal involvement in the learning of adolescents with ADHD and have implications for involving fathers in interventions aimed at improving their academic achievement.